Changes in the VAT burden on expenses of selected households in the Czech Republic (2007-2014) - Regína Strílková; Jan Široký (DANUBE: Law, Economics and Social Issues Review, 2015)
The Czech Republic is a typical representative EU Member State which has several times changed VAT rates during the analyzed period 2007-2014 in an effort to consolidate the public budget. These changes are reflected in household spending, which were analyzed by means of the consumer basket, the composition of which is also undergoing changes. Another factor that has an impact on household expenditures is the transfer of commodities between the reduced and standard rate of VAT. The final factor used is the differentiation of households according to their income levels. The aim of this paper is to determine how these changes took effect in the Czech Republic in the share of consumption of commodities included in the standard and reduced VAT rates and in exempt transactions according to household income groups in the analyzed period 2007-2014 and to determine the impact of these changes on the tax burden on selected households by value added tax and confirmation of the assumption of VAT regressivity.
Keywords: 330; VAT Rates; Household Expenditures; Tax Burden; VAT Regressivity